Severe Asthma and Allergy: A Pediatric Perspective - Arasi, Stefania; Porcaro, Federica; Cutrera, Renato; Fiocchi, Alessandro G. (Frontiers in Pediatrics, 2019)
Severe asthma in children is associated with significant morbidity and lung function decline. It represents a highly heterogeneous disorder with multiple clinical phenotypes. As its management is demanding, the social and economic burden are impressive. Several co-morbidities may contribute to worsen asthma control and complicate diagnostic and therapeutic management of severe asthmatic patients. Allergen sensitization and/or allergy symptoms may predict asthma onset and severity. A better framing of “allergen sensitization” and understanding of mechanisms underlying progression of atopic march could improve the management and the long-term outcomes of pediatric severe asthma. This review focuses on the current knowledge about interactions between severe asthma and allergies.